The determinants of capital structure on textile industry in Pakistan / Noraini Junah - Junah, Noraini (2020)
Textile is one of the leading manufacturers in Pakistan and is a major contributor to the economy. It has been the country's backbone as it provides employment and export revenues to the countries. Export of textile will help in the development of the industry. The poor law, energy crisis, rising cost of raw materials and production cost, lack of modem equipment's and R&D institution that occur on the year 2013 have significantly contributed to the decline of textile sector. In this study is more focused to investigate the performance of 16 textile industries in Pakistan by using the macroeconomic factors which are gross domestic product (GDP), interest rate (IR), market capitalization (MC), public debt (PD), exchange rate (ER) and corporate tax (CT) with the duration from the year 2010 until 2018 to analyse the effect of macroeconomic factors towards capital structure on textile industries in Pakistan. The result of the study is positive relationship public debt with capital structure while exchange rate has a negative relationship with capital structure on textile industry in Pakistan. Gross domestic product, interest rate, market capitalization and corporate tax have no relationship with capital structure.